ARM STM32F4 Microcontroller Implementation for Control and Modeling of BLDC Motor : Implementasi Mikrokontroler ARM STM32F4 untuk Kontrol dan Pemodelan Motor BLDC - Anshory, Izza; Wisaksono, Arief; Sulistiyowati, Indah (Universitas Muhammadiyah Sidoarjo, 2022)
Brushless Direct Current (BLDC) motor as an electric vehicle driving motor, its speed control is directly proportional to the voltage applied to its terminals. Therefore the applied average voltage or the average current flowing through the motor will change depending on the duty cycle of the ON and OFF time of the pulses, so the motor speed will change. The purpose of this research is to apply the ARM STM32F4 microcontroller to control the speed of the BLDC motor and obtain the transfer function equation of the BLDC motor. The method used in this study is an ARM STM32F4 microcontroller generating a duty cycle through Pulse Width Modulation (PWM) control which causes changes in the ON and OFF switches of the three-phase inverter. The variable change data is then modeled mathematically in the form of a transfer function using the System Identification Toolbox (SIT) application in Mathlab programming. The results of calculations and tests show that the ARM STM32F4 microcontroller functions well in regulating the rotational speed of the BLDC motor.